Social Support and Self Disclosure Linked to Lower Quarter Life Crisis: Dukungan Sosial dan Pengungkapan Diri Terkait dengan Krisis Kehidupan Kelompok Bawah - Moh Idang Purnama; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Early adulthood is a transitional phase involving identity formation, career preparation, and psychological adjustment. Specific Background: Fresh graduates often face emotional uncertainty and life decision challenges associated with quarter life crisis. Knowledge Gap: Empirical studies rarely examine social support and self disclosure simultaneously as correlational predictors of quarter life crisis among fresh graduates. Aims: This study examined relationships between social support and self disclosure with quarter life crisis among fresh graduates aged 22–24 years in Sidoarjo. Results: Using a quantitative correlational design with purposive sampling, 270 participants were analyzed through multiple linear regression. Significant negative correlations were found between social support and quarter life crisis (r = −0.594, p < 0.001) and between self disclosure and quarter life crisis (r = −0.530, p < 0.001). Simultaneous testing showed significant association (F = 88.469, p < 0.001), with both predictors explaining 39.9% of variance. Most participants demonstrated moderate levels across measured variables. Novelty: This study integrates interpersonal support and personal openness within a single regression analysis focusing on fresh graduates. Implications: The findings highlight the relevance of interpersonal networks and personal openness in psychological support strategies for early adulthood transition among fresh graduates. Highlights: Correlation Testing Demonstrated Significant Inverse Coefficients Across Both Predictor Variables. Majority of Participants Were Classified Within Moderate Psychological Transition Levels. Combined Predictors Accounted for 39.9% of Variance in Emotional Transition Outcomes. Keywords: Quarter Life Crisis, Social Support, Self Disclosure, Fresh Graduates, Multiple Regression